Pengaruh berbagai Tingkat Lisin dan Metionin yang dibutuhkan Puyuh Jepang (Coturnix-Coturnix Japonica) terhadap Produksi Telur - Dwi Margi Suci; R Abdelsamie (Buletin Ilmu Makanan Ternak, 1991)
The aim of this experiment was to get some information concerning lysine and methionine requirements for egg production. Five weeks of age of Female Japanese Quail were subjected to 9 treatments. The treatments were 3 levels of lysine (1.39%; 1.18%; 0.92%) and 3 level of methionine (0.55%; 0.45%; 0.35%). The basal diets were isocaloric and isonitrogenous. Egg production was significantly increased by lysine (P<0.05) as well as methionine (P<0.01). The highest production was achieved by a combination of 1.38% lysine and 0.55% methionine. However, the treatments did not influenced feed consumption and feed conversion.